Efek Terapi Musik dalam Menurunkan Kecemasan Pasien Selama Pemeriksaan MRI - I Putu Very Triana Putra; I Kadek Yuda Astina; Triningsih Triningsih (Jurnal Kesehatan Medika Udayana, 2022)
Background: Anxiety is a normal response in the face of stress which is characterized by feelings of fear accompanied by somatic signs. The patient's anxiety in the MRI examination arises because he knows he will receive medical treatment related to the use of radiation that will cause adverse effects that cause infertility or cancer. The purpose of this study was to determine the effect of music therapy in reducing anxiety when undergoing an MRI examination. Method: The design of this study used a posttest only intervention group design. The study was conducted on 18 July – 12 August 2022 in the MRI Room of the Bali Mandara Hospital, Bali Province. The sample was 72 people who were divided into 2 intervention and control groups. The inclusion criteria of this study were patients with head first examination position, age above 18 years. Exclusion criteria were patients with decreased consciousness, hearing loss and weight above 150 kg. The research instrument used the MRI-AQ questionnaire, and the Mann Whitney statistical test. Result: The results showed that most of the respondents were 46-55 years old (33.3%), most of the MRI examinations were Lumbo sacral type (54.2%), and the level of anxiety was mostly mild (91.6%). The results of the normality test of data <0.05 so that the data is not normally distributed. The Mann Whitney test was conducted to determine the effect of music therapy and obtained p = 0.001 indicating there was a significant difference between the intervention group and the control group. Conslusion: The intervention of providing music therapy to patients undergoing MRI examination has an effect in reducing patient anxiety, especially in patients undergoing MRI examination. Music makes the examination more pleasant for the patient. Music causes positive changes in the environment and distracts from the examination, relaxing the patient.